Two new iassine leafhopper genera from Ecuador (Hemiptera: Cicadellidae) - Krishnankutty, Sindhu M.; Dietrich, Christopher H. (Zootaxa, 2012)
Two new iassine leafhopper genera, Nigrojassus gen. nov. and Neotrocnada gen. nov. (Hemiptera: Cicadellidae) from Ecuador are described and illustrated. Nigrojassus gen. nov. is closely related to Hoplojassus Dietrich based on the elongate scutellum, arcuate base of the hindwing, leg chaetotaxy and flattened subgenital plate. Two new species, N. madhurai sp. nov. and N. ananthi sp. nov. are described in the genus. Neotrocnada is a monotypic genus with Neotrocnada napoensis sp. nov. as type species. Homologies of the highly modified structures of the male genitalia of Neotrocnada are assessed based on comparison to other New World genera.